Representation of Hegemonic Masculinity (A Semiotic Analysis of Roland Barthes in the Film Women from Rote Island) - Engelbert, Sheron; Palupi, Merry; Sadono, Teguh (Indonesian Journal Publisher, 2026)
The film Women from Rote Island (2023) depicts women's struggles on Rote Island facing repeated sexual violence in a strong patriarchal society. This study analyzes the representation of hegemonic masculinity using Roland Barthes' semiotic theory through the stages of denotation, connotation, and myth. The findings show that male characters as perpetrators are represented as symbols of dominant power that normalize control over women's bodies through physical and social violence. The myth of patriarchy is portrayed as a system perpetuating women's subordination, while Orpa and her daughters' resistance begins to deconstruct this hegemony. This research emphasizes the importance of myth deconstruction to promote gender equality in indigenous communities.